Staff perspectives: What is the function of adult mental health day hospital programs?. Issue 8 (24th August 2017) - Taube‐Schiff, Marlene; Ruhig, Megan; Mehak, Adrienne; Deathe van Dyk, Melanie; Cassin, Stephanie E.; Ungar, Thomas; Koczerginski, David; Sockalingam, Sanjeev
Accessible summary: What Is Known on the Subject?: Psychiatric day hospital (DH) treatment has been offered since the 1930s and is appropriate for individuals experiencing intense psychiatric symptoms without requiring 24‐hour inpatient care. No empirical research has examined the specific purpose of DH treatment from the perspectives of healthcare providers within these programs. What This Paper Adds To Existing Knowledge?: This study was the first to address the question of the purpose and function of DH treatment from the outlook of frontline workers within this setting, and confirmed anecdotal observations that DH treatment provides an alternative to intensive psychiatric care, and also operates as "bridge" between these intensive services and purely outpatient treatment. Additional information emerged, such as the importance of the name of DH programs avoiding connotations of illness, the benefits and skills that draw patients to these programs, and challenges that staff and patients experience within DH programs (e.g. short length of treatment, barriers to treatment access). What Are the Implications for Practice?: This information can enhance curriculum development within these settings. For example, given the importance of skill building, it is essential to integrate the provision of skill building and coping strategies within these settings. In addition, given that the name of the setting can impact staff (and perhaps service users as well), ensuring that the name of such program highlight wellness and recovery may enable a different type of therapeutic community to develop within these settings. Abstract: Introduction: Despite the benefits of psychiatric day hospitals (DH), research has not addressed staff perspectives of these programs' effectiveness and barriers. Aim: To elucidate staff perceptions of Adult Mental Health DH programs at two hospitals in Canada, allowing for improved programming, enhanced structure and increased understanding of DH settings within the continuum of care. Method: Twenty‐five DH staff members completed semi‐structured qualitative interviews. Two independent coders applied content analysis to achieve data saturation. Results: Four major themes emerged: (1) program purpose and function, (2) what is in a name, (3) perceived patient motivation, and (4) room for improvement. Discussion: Findings highlighted the importance of a multidisciplinary team delivering education and skill‐focused interventions. Services were cited as "bridging" different mental health settings. Challenges included barriers to treatment access and inadequate length of treatment. Implications for Practice: Understanding the function and purpose of this treatment service may enhance service delivery by enabling programs to integrate identified key ingredients. Providers can also note treatment duration and consider how to best use that time. Finally, language used within a DH setting appears to impact staff delivering services, and may also alter patients' understanding of the services they will receive and purpose of the program.